Response of ecosystem intrinsic water use efficiency and gross primary productivity to rising vapor pressure deficit - Quan Zhang; Darren L Ficklin; Stefano Manzoni; Lixin Wang; Danielle Way; Richard P Phillips; Kimberly A Novick (Environmental Research Letters, 2019)
Elevated vapor pressure deficit (VPD) due to drought and warming is well-known to limit canopy stomatal and surface conductance, but the impacts of elevated VPD on ecosystem gross primary productivity (GPP) are less clear. The intrinsic water use efficiency (iWUE), defined as the ratio of carbon (C) assimilation to stomatal conductance, links vegetation C gain and water loss and is a key determinant of how GPP will respond to climate change. While it is well-established that rising atmospheric CO _2 increases ecosystem iWUE, historic and future increases in VPD caused by climate change and drought are often neglected when considering trends in ecosystem iWUE. Here, we synthesize long-term observations of C and water fluxes from 28 North American FLUXNET sites, spanning eight vegetation types, to demonstrate that ecosystem iWUE increases consistently with rising VPD regardless of changes in soil moisture. Another way to interpret this result is that GPP decreases less than surface conductance with increasing VPD. We also project how rising VPD will impact iWUE into the future. Results vary substantially from one site to the next; in a majority of sites, future increases in VPD (RCP 8.5, highest emission scenario) are projected to increase iWUE by 5%–15% by 2050, and by 10%–35% by the end of the century. The increases in VPD owing to elevated global temperatures could be responsible for a 0.13% year ^−1 increase in ecosystem iWUE in the future. Our results highlight the importance of considering VPD impacts on iWUE independently of CO _2 impacts.